A Phytochemical Profile and Acute Toxicity of Meistera aculeata (Roxb). Skornick. & M.F. Newman Fruits (Zingiberaceae) - Hendrisno Hendrisno; Megawati Megawati; Agusriyadin Agusriyadin; Sabandar Carla Wulandari (Hasanuddin University, 2023)
Meistera aculeata (Roxb). Skornick. & M.F. Newman belongs to the ginger family (Zingiberaceae) and locally known as ‘Susube’ by natives of Konawe district of Southeast Sulawesi. M. aculeata is an endemic plant and its fruit has been consumed by the locals. Until today, study on chemistry and biological activity aspects of M. aculeata has yet investigated. Hence, this research aimed to identify phytochemical contents and acute toxicity of M. aculeata fruits extracted using ethanol as the solvent. Phytochemical screening showed the accumulation of alkaloids, tannins, flavonoids, terpenoids, and saponins in the ethanol extract of M. aculeata fruits. Meanwhile, the Brine Shrimp Lethality Test (BSLT) revealed that ethanol extract of M. aculeata fruits has a weak acute toxicity (LC50 683,9 ppm) when compared with potassium dichromate as the positive control of the assay (LC50 8,3 ppm). The study concluded that M. aculeata fruits could be used in the development of drugs from natural sources.